A Customized Next-Generation Sequencing-Based Panel to Identify Novel Genetic Variants in Dementing Disorders: A Pilot Study. (18th August 2020) - Lanza, Giuseppe; Calì, Francesco; Vinci, Mirella; Cosentino, Filomena Irene Ilaria; Tripodi, Mariangela; Spada, Rosario Sebastiano; Cantone, Mariagiovanna; Bella, Rita; Mattina, Teresa; Ferri, Raffaele
Abstract : Purpose . The advancements in the next-generation sequencing (NGS) techniques have allowed for rapid, efficient, and cost-time-effective genetic variant detection. However, in both clinical practice and research setting, sequencing is still often limited to the use of gene panels clinically targeted on the genes underlying the disease of interest. Methods . We performed a neurogenetic study through an ad hoc NGS-based custom sequencing gene panel in order to screen 16 genes in 8 patients with different types of degenerative cognitive disorders (Alzheimer's disease, mild cognitive impairment, frontotemporal dementia, and dementia associated with Parkinson's disease). The study protocol was based on previous evidence showing a high sensitivity and specificity of the technique even when the panel is limited to some hotspot exons. Results . We found variants of the TREM2 and APP genes in three patients; these have been previously identified as pathogenic or likely pathogenic and, therefore, considered "disease causing." In the remaining subjects, the pathogenicity was evaluated according to the guidelines of the American College of Medical Genetics (ACMG). In one patient, the p.R205W variant in the CHMP2B gene was found to be likely pathogenic of the disease. A variant in the CSF1R and SERPINI1 genes found in two patients was classified as benign, whereas the other two (in the GRN and APP genes) were classified as likely pathogenic according to the ACMG. Conclusions . Notwithstanding the preliminary value of this study, some rare genetic variants with a probable disease association were detected. Although future application of NGS-based sensors and further replication of these experimental data are needed, this approach seems to offer promising translational perspectives in the diagnosis and management of a wide range of neurodegenerative disorders.